2018
DOI: 10.1667/rr15028.1
|View full text |Cite
|
Sign up to set email alerts
|

Charged-Iron-Particles Found in Galactic Cosmic Rays are Potent Inducers of Epithelial Ovarian Tumors

Abstract: Astronauts traveling in deep space are exposed to high-charge and energy (HZE) particles from galactic cosmic rays. We have previously determined that irradiation of adult female mice with iron HZE particles induces DNA double-strand breaks, oxidative damage and apoptosis in ovarian follicles, causing premature ovarian failure. These effects occur at lower doses than with conventional photon irradiation. Ovarian failure with resultant loss of negative feedback and elevated levels of gonadotropin hormones is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The tumors were tubular adenomas or mixed tubular adenoma/granulosa cell tumors. Though conclusions are limited by the dose rate, this study demonstrated a that space radiation analog can induce ovarian tumors in mice, raising concerns about ovarian tumors as late sequelae of deep space travel in female astronauts [142].…”
Section: Radiationmentioning
confidence: 83%
“…The tumors were tubular adenomas or mixed tubular adenoma/granulosa cell tumors. Though conclusions are limited by the dose rate, this study demonstrated a that space radiation analog can induce ovarian tumors in mice, raising concerns about ovarian tumors as late sequelae of deep space travel in female astronauts [142].…”
Section: Radiationmentioning
confidence: 83%
“…Further, the forms of secondary radiation, triggered by GCRs, still possess significant penetrative potential and can accumulate more efficiently in biological tissues, as compared to primary GCRs (Slaba et al, 2017). GCR secondary radiation particles include beta particles, alpha particles, gamma rays, x-rays, neutrons, protons, and other particles with greater charge and mass (Mishra et al, 2018).…”
Section: Galactic Cosmic Raysmentioning
confidence: 99%
“…In vivo studies on low‐energy radiation from GCR observed stimulation of ovarian tumor formation in rat models (Mishra et al, 2018). Additionally, GCRs high penetrative capabilities make it possible for them to compromise central nervous system (CNS) structures and function.…”
Section: Space Radiationmentioning
confidence: 99%
“…HZE nuclei may strongly contribute to the carcinogenic risk to which crew members are exposed. Indeed, even at relatively low energy, iron ions are shown to be potent inducers of ovarian tumors formation in rodents [18]. Due to their high penetration power, GCR can efficiently reach CNS cells and pose a major risk to CNS function.…”
Section: Space and Space-relevant Radiationmentioning
confidence: 99%